Primary primitive neuroectodermal tumor of the ovary - Torres-Cepeda, Duly (2022)
Primitive neuroectodermal tumor of the ovary is a rare and aggressive small roundcell soft tissue sarcoma of neural origin that is usually associated with high morbidityand mortality. Immunohistochemistry is a useful adjunct in the differential diagnosis.We describe a case of a primitive neuroectodermal tumor of the ovary in a 21-yearold nulliparous patient who reported pain and increased abdominal circumference.Ultrasonography showed a solid-cystic heterogeneous tumor apparently originatingfrom the left adnexa. Magnetic resonance imaging confirmed the presence of atumor extending into the left iliac fossa without local organ involvement or regionalor distant metastases. Tumor markers were all within the normal range. Duringlaparotomy, a left ovarian tumor was observed with a normal right ovary. Leftsalpingo-oophorectomy was performed due the size of the tumor, right ovarianwedge resection, pelvic lymphadenectomy and omentectomy. Histopathologicexamination revealed tumor composed of sheets of round cells. The tumor cells werepositive for chromogranin A, synaptophysin, vimentin and neuron-specific enolase,which confirmed the diagnosis of a primitive neuroendocrine tumor of the leftovary originating from immature cystic teratoma. The patient refused postoperativechemotherapy.